Ultrasonic Measurement of Kidney Length in Nepalese People (Journal of Nepal Physical Society, 2017)
Ultrasonography (USG) is a major modality to determine the dimension of internal body parts and foreign materials that enters into the tissue. This modality can measure the accurate value of the size of organs because it has no magnification property. This measurement based on the sound pulse to travel to the object and the echo to return back. In the present study, the ultrasonographic kidney length is determined in individuals without known renal disease. The experiment is done 504 patients (214 males and 290 females) who came to Tribhuvan University Teaching Hospital (TUTH) from May 2001 to August 2001. The average kidney size of Nepalese people was found (9.48 0.96) cm. The kidney length was found maximum in the age range around 40 years and observed approximately not changing significantly up to the age of 60 and decreasing from the age range 60 years. Moreover, average kidney size of male is found to be greater than the female of same age group.Journal of Nepal Physical SocietyVolume 4, Issue 1, February 2017, Page: 49-53